Milk Man: Investigating the Effectiveness of a Socially Connected Breastfeeding App Targeting Fathers - White, Becky Kate (Curtin University, 2018)
Breastfeeding is the ideal first food for infants and fathers are important in influencing breastfeeding initiation and duration. Mobile technology offers opportunity to reach and engage people in interventions. This study investigated the impact Milk Man, a father-focused socially connected, gamified app about breastfeeding, had on exclusive breastfeeding duration. The findings provide valuable insight into the acceptability of the engagement strategies, and demonstrate a father-focused app is an acceptable approach that impacts positively on breastfeeding.